To study on the effect of tuning rules used on the water level controllability - Ismail, Arif Iskandar (2017)
The purpose of this research is to study on the effect of tuning rules used to recover from disturbances for the liquid level controllability. This research extract the information upon mostly primary sources including books, published journals, and experiments in laboratory. In the experiment, the time will indicate the respond of PV whether it is fast or slow if the controller output is changed. Time is observed by several tuning methods which are Ziegler-Nichol’s tuning rule, tuning rule by Takahashi and tuning rule by Chien, Hrones and Reswick (CHR). The Water Level Control Using PID Controller is a design of an intelligent automatic level measurement system using PID controller. The system will allow users to measure and set the desired level of water with the PID controller controlling the process of water flowing into the tank. The system will be connected with a control valve and level sensor for the control section. The system is able to show the trend of water flowing into the tank and the responses of the measurements. The PID controller has the ability to control the trend and specific responses for a smooth transition of the water reaching the desired level point with the tunings and algorithm parameters entered by the handler (human) together with safety aspects monitored by the PID controller especially in hazardous plant